Cigarette smoking and duration of sun exposure as risk factor for cataract formation - Reinne Natali Christine; Abigail Serapina; Gilbert Simanjuntak; Janes Fritz Tan (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2020)
Cataract is the most common cause of vision loss in Indonesia. It involves many risk factors, such as age, trauma, persistent intra-ocular inflammation, ultraviolet radiation, diabetes mellitus, hypoparathyroidism, prolonged corticosteroid administration, and high body mass index. However, the role of smoking and sun exposure in cataracts has received less attention despite of the high number of cigarette smokers in Indonesia and this country also has strong sunshine all year round. The aim of this study was to investigate the relationship of cigarette smoking and duration of sun exposure with senile cataracts in Jakarta, Indonesia. This was a cross-sectional study without knowing risk factor before. A total of 100 patients participated in this study selected with consecutive sampling technique. They were divided into two groups: first was the case group consisting of 50 subjects aged more than 40 years old and diagnosed with senile cataracts and the second was the control group consisting of subjects aged more than 40 years old without cataract disease. All participants had to complete the questionnaire related to the history of smoking and duration of outdoor activity per day as it related to sun exposure. The sample was taken from the eye screening program in Puskesmas Cawang, East Jakarta. This research discovered a relationship between cigarette smoking and duration of sun exposure more than seven hours per day with the incidence of senile cataract (p=0.001) Statistical tests also showed an association between smoking duration more than 20 years and incidence of senile cataract (OR 7.25, 95% CI: 1.43 - 36.6; p = 0.02). However, the results revealed that there was no relationship between the number of cigarettes smoked per day with the incidence of senile cataract (p = 0.915). Overall, cigarette smoking and its duration appear to increase the risk of senile cataract formation.